Effects of Phaleria macrocarpa and Averrhoa bilimbi L. on fasting blood glucose in diabetic rats - Laila Sholehah; Fathurrahman Fathurrahman; Niken Widyastuti Hariati; Aprianti Aprianti (Institute of Advanced Engineering and Science, 2026)
Traditional ingredients have been proven to contain many substances that can be used to prevent and treat diabetes. This study aimed to investigate the effects of a combination of Phaleria macrocarpa and Averrhoa bilimbi L. extracts on fasting blood glucose levels. A randomized, post-test-controlled group design was used. Type 2 diabetes mellitus was induced in 36 Sprague Dawley rats by feeding them a high-fat diet for 2 weeks, followed by the administration of streptozotocin (STZ) and nicotinamide to induce type 2 diabetes mellitus. The rats were divided into six groups. The treatment was administered for 21 days, and fasting blood glucose levels were measured. The data were analyzed using one-way analysis of variance (ANOVA). The combined dose of Phaleria macrocarpa and Averrhoa bilimbi L. extract effectively reduced fasting blood glucose levels over 21 days. Group T1 demonstrated the highest efficacy and did not differ significantly from that of the C+ group. The effective dosage that influenced fasting blood glucose levels was a combination of Phaleria macrocarpa at 750 mg/kg W/day and Averrhoa bilimbi L. at 375 mg/kg. Phaleria macrocarpa and Averrhoa bilimbi L. extract have a synergistic effect, making them a promising natural medication for controlling blood glucose levels.